Examining the influence of leader’s emotional intelligence on employee organizational citizenship behaviours in Malaysia - Yunus, Noorlaila; Hassan, Che Norlia; Amir Ishak, Noormala; Ali, Abdul Jalil (2008)
Emotional intelligence (EI) has been an important issue being debated these days particularly among the organizational settings. Past literatures have found that subordinates were not passive, but rather proactive participants who would try their best to change their work environment.The issues concerning EI are generating increasing interest in the field of leadership studies as researchers attempt to identify the qualities that predict effective leaders. Since it has been established that EI affects work behaviours namely job performance, job satisfaction, loyalty, encourage employee displaying OCB and many positive impacts, this is the time now where management should consider EI in the workplace.Firstly, the HR people must take actions on the importance of EI. During the recruitment and selection process, the applicants at least must have moderate EI. New employees with high emotional awareness and regulation should be hired (Jordan, Ashkanasy, & Hartel, 2002; Leidner, 1999). Organizations also should apply EI training to the employees, to develop their soft skills. Given that EI abilities can be developed, training in specific facets of EI; appraising, understanding emotions and managing in self and others as well as utilizing emotions to facilitate performance would guarantee that the support staffs perform their job performance as expected by the management. Training in EI is proven to enhance good work behaviours (Bardzil & Slaski, 2003). Emotional intelligence leaders are though to be happier and more committed to their organization (Abraham, 2000), achieve greater success (Miller, 1999),perform better in the workplace (Goleman, 1998), take advantage of and use positive emotions to envision major improvements in organizational functioning (George, 2000), and use emotions to improve their decision making and instil a sense of enthusiasm, trust and co-operation in other employees through interpersonal relationships(George, 2000). Malaysian leaders need to develop EI to better influence their employees. While employees play the vital role to determine the success of the organization, the important placed on the human factor has always been a key success factor in any organization throughout the years. Success depends on involving the workforce’s entire capacity to generate good work behaviours and ways of working to outsmart the competitors. Hence, a leader plays the utmost important to achieve the goals of success of the organization. The primary motivation of this study is to focus on how the leader’s EI influence the employee work behaviours specifically organizational citizenship behaviours (OCB). In this study, excellent work behaviours was found to be an important indicator as the quality of the employees work influences the organization’s product and services.Leaders who have the capacity to display their care and concern appears to be able to positive and concern, maintaining positive moods, support and display fair treatment and respect for others (Fombrun, 2000 ).